Heavy metal tracing from gold mining soil to vinasse in the downstreaming process of sweet sorghum to bioethanol - Mohammad Nurcholis; Dwi Fitri Yudiantoro; Soeranto Human; Erni Johan; Kristin Natalia H Makahenggang; Laponda Jaya Katon; Firdaus Muhammad Fauzi (Universitas Sebelas Maret, 2025)
Soils in gold mining areas have the potential to contain heavy metals from rock weathering. Such soil was planted with sweet sorghum to increase land productivity in Boto Village, Wonogiri Regency, Central Java during the dry season. The harvested crop was not used for food, but processed into biofuels through fermentation and distillation. Accordingly, the aim of this research was to trace the presence of several heavy metals in vinasse, a by-product of sweet sorghum stem juice fermentation process, from plants grown on soil in a community of gold mining area. Two varieties of sweet sorghum, Samurai 1 and Samurai 2, were cultivated on this soil. Then, they were harvested and the sorghum stem extract was fermented to produce ethanol. Distillation process was carried out on the fermented juice to increase the ethanol concentration, leaving behind vinasse. Chemical analysis was carried out on the chemical properties of the soil (pH, CEC, Organic-C, total-N, available-K, and potential-P), and content of the heavy metals of Fe, Mn, Pb, and Cu in the soil, juice, and vinasse. The soil exhibits a neutral reaction, low salinity, organic-C, total-N, available P and CEC. The levels of Fe, Mn, Pb, and Cu in soil are 7.8%, 0.1%, 76.00 ppm, 23.81 ppm. In the juice, these concentrations were 9.66, 21.14, 1.49, 1.64 in ppm. In the vinasse, they were 5.29, 28.15, 1.05, 0.73 ppm, respectively. These results indicate that heavy metals in soils could be absorbed by sorghum crops and they were absorbed in the stems of Samurai 1 and 2 sweet sorghum varieties, extracted into the juice, and partially remained in the vinasse.